Pengelolaan Pembelajaran PAI Model Full Day di SMP Plus Darus Sholah Jember: Management of Islamic Religious Education Learning with Full Day Model at SMP Plus Darus Sholah Jember - Mashudi Mashudi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2017)
The implementation of Islamic Religious Education (PAI) in schools still faces challenges in shaping students' religious behavior due to limited time, methods, and teacher professionalism. This study aims to analyze the learning management of PAI with a full-day school model at SMP Plus Darus Sholah Jember, focusing on scheduling, progress notes, motivation, and learning control. A descriptive-qualitative approach was employed, involving observation, in-depth interviews, and documentation. The findings reveal that PAI scheduling follows annual and extra-school programs, including calligraphy, scouts, Qur'an reading, and sports. Student progress is recorded through teacher notes, mid-term and semester reports, and behavioral records. Motivation is fostered through verbal and non-verbal self-evaluation and reinforcement. Learning control, including media, structure, and evaluation, is fully managed by the foundation. The study concludes that the full-day model enables more integrated PAI learning but remains teacher-dominated, with limited student autonomy. It is recommended that teachers deepen their theoretical understanding of learning strategies and optimize the use of media and facilities to enhance religious character formation. Pembelajaran Pendidikan Agama Islam (PAI) di sekolah masih menghadapi tantangan dalam membentuk perilaku beragama peserta didik akibat keterbatasan waktu, metode, dan profesionalisme guru. Penelitian ini bertujuan menganalisis pengelolaan pembelajaran PAI model full day di SMP Plus Darus Sholah Jember, mencakup penjadwalan, catatan kemajuan, motivasi, dan kontrol belajar. Pendekatan deskriptif-kualitatif digunakan melalui observasi, wawancara mendalam, dan dokumentasi. Temuan menunjukkan bahwa penjadwalan PAI sesuai program tahunan dan ekstrakurikuler Sabtu meliputi kaligrafi, pramuka, baca Al-Qur’an, dan olahraga. Catatan kemajuan siswa berupa buku guru, rapor tengah semester dan semester, serta catatan perilaku. Motivasi dibangun melalui evaluasi diri verbal dan non-verbal serta pemberian penguatan. Kontrol belajar, termasuk media, struktur, dan evaluasi, sepenuhnya berada di tangan yayasan. Kesimpulannya, model full day memungkinkan pembelajaran PAI lebih terintegrasi namun masih didominasi guru dengan kebebasan siswa terbatas. Disarankan agar guru memperdalam teori strategi pembelajaran serta mengoptimalkan media dan fasilitas pendukung.